From a Non-Integrated Territory to a Metropolitan Park The West Area of Santa Fe (Argentina) - Mirta Soijet; Yanina Uriarte (International Journal of Built Environment and Scientific Research, 2017)
This paper presents and describes the city of Santa Fe (Argentina) and specially the west area characterized by the dominant presence of water. The evolution of that city establishes a constant battle to "gain ground" to the river invading many times its valley of flood and requiring works of infrastructure to contain its attempts to recover it. It is possible to recognize a contradiction -due to vulnerability- between crisis (risk) and opportunity (environmental sustainability). Explained this proposition and the terrible events happened in 2003 and 2007, it`s necessary to think in the integration of water containment to the landscape thought in cultural terms. Once this basic question has been submitted, and after reviewing the available project background, it is proposed to think and Project the integration to the city of this sector (served as a reservoir for excess rainwater) and its characterization as a metropolitan park district proposing the strategies to be considered.